Hukum Pembatalan Kontrak dalam Perspektif Fiqh Muamalah - Afrida, Yenti (Ijtihad, 2015)
This paper titled, "contact cancellation law in Fiqh Muamalah Perspective". This discussion is motivated by the current economic system that applies the rules to bind the parties contract, so that in the event od cancellation of the contract, if any, between on party can be minimized. Forms of contract are likely occurrence of such cancallation is selling tickets, where the customer after buying a ticket sometimes cancel and request a refund of the ticket price diverse reasons. Another form is cancellation of the contract which resulted in a scorching or advances that have benn deposited when the transaction did not take a place. Such problems often occur in the middle of the community and need to be studied law. After doing research on fiqh muamalah and see the reality thar occurs in the community, the cancellation of the contract with the price cuts and the loss of advance cancellation allowed and not against the law in fiqh studies muamalah.